2020
DOI: 10.1021/acs.jmedchem.0c00976
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Nitrones Design for Stroke Treatment

Abstract: The recent advances of tetramethylpyrazine nitrones and quinolylnitrones for the treatment of stroke have been reviewed and compared with other agents, showing promising therapeutic applications. As a result of a functional transformation of natural product ligustrazine, (Z)-N-tert-butyl-1-(3,5,6-trimethylpyrazin-2-yl)methanimine oxide ( 6) is a multitarget small nitrone showing potent thrombolytic activity and free radicals scavenging power, in addition to nontoxicity and blood−brain barrier permeability. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 82 publications
0
28
0
2
Order By: Relevance
“…Consequently, nitrones were initially used because they have extremely potent activity in biological systems, mainly due to their free radical "spin trap" capacity. Subsequent studies have shown that alpha-phenyl-N-tertbutylnitrone(PBN) nitrone, as well as its analogs demonstrated low toxicity and potent pharmacological activity against Parkinson's disease and Alzheimer's (Floyd et al, 2008(Floyd et al, , 2013 and ischemic stroke (Contelles, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, nitrones were initially used because they have extremely potent activity in biological systems, mainly due to their free radical "spin trap" capacity. Subsequent studies have shown that alpha-phenyl-N-tertbutylnitrone(PBN) nitrone, as well as its analogs demonstrated low toxicity and potent pharmacological activity against Parkinson's disease and Alzheimer's (Floyd et al, 2008(Floyd et al, , 2013 and ischemic stroke (Contelles, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of stable and persistent nitroxide adducts of free radical reactive species endows nitrones with marked antioxidant properties and support their use as therapeutic agents to treat disorders related to oxidative stress. [1][2][3] The same process promotes the use of nitrones as building blocks for the construction of nitrogenous compounds 4 and as electron paramagnetic resonance (EPR) spin traps. 5 Although natural products containing the nitrone functional group are scarce, 6 antioxidant and pharmacologically active compounds of natural origin can be used as starting materials for the semisynthesis of novel nitrones with high potential for application.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The nitrone derivatives of ligustrazine, a pyrazine found in the Chinese herb Ligusticum wallichii Franch., have antioxidant and thrombolytic properties and are effective therapeutics for treating ischemic stroke. 3 Another example is the nitrone derived from the water-soluble analogue of vitamin E, Trolox, which shows enhanced radical scavenging and neuroprotective properties. 9 Betalains are non-toxic water-soluble pigments found in plants, fungi and bacteria 10 that have been consumed in foods for millennia.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of stable and persistent nitroxide adducts of free radical reactive species endows nitrones with marked antioxidant potential and supports their use as therapeutic agents to treat disorders related to oxidative stress. [1][2][3] The same process promotes the use of nitrones as building blocks for the construction of nitrogenous compounds 4 and as electron paramagnetic resonance (EPR) spin traps. 5 Although natural products containing the nitrone functional group are scarce, 6 antioxidant and pharmacologically active compounds of natural origin can be used as starting materials for the semisynthesis of novel nitrones that have many potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The nitrone derivatives of ligustrazine-a pyrazine found in the Chinese herb Ligusticum wallichii Franch.-have antioxidant and thrombolytic properties and are effective therapeutics for treating ischemic stroke. 3 Another important example is the nitrone derived from the water-soluble analog of vitamin E (Trolox), which shows enhanced radical scavenging and neuroprotective properties. 9 Betalains are non-toxic water-soluble pigments found in plants, fungi, and bacteria 10 that have been consumed for millennia.…”
Section: Introductionmentioning
confidence: 99%